The efficacy of EndoActivator, passive ultrasonic irrigation, and Ultra X in removing calcium hydroxide from root canals: an in-vitro study - Alireza Adl; Alireza Razavian; Fateme Eskandari (BMC, 2022)
Abstract Background This study aimed to compare the efficacy of EndoActivator, passive ultrasonic irrigation, and Ultra X in removing calcium hydroxide from the artificial grooves in root canal walls. Methods The root canals of 50 extracted human maxillary incisors were instrumented by using the ProTaper rotary system up to #F4 (size 40/0.06 ProTaper) and the teeth were split longitudinally. Lateral grooves were created in the apical and coronal parts of one half and the middle part of the other half. Calcium hydroxide paste was applied to the grooves and the root halves were reassembled. After seven days, the calcium hydroxide was removed from the canal by using one of the EndoActivator, passive ultrasonic irrigation, and Ultra X devices; one group went without irrigation (control group). The CH remnants in the grooves were scored at 20× magnification. The data were analyzed by using the Kruskal-Wallis, Dunn's post hoc, and Friedman tests. P < 0.05 was considered to be statistically significant. Results No statistically significant difference existed among the experimental groups at the coronal and middle grooves (P > 0.05). However, Ultra X was significantly more effective than passive ultrasonic irrigation at the apical grooves (P = 0.023). Conclusion Within the limitations of this study, Ultra X can be reported to remove the calcium hydroxide from the apical third more efficiently than passive ultrasonic irrigation.